1981
DOI: 10.1016/0341-8162(81)90006-0
|View full text |Cite
|
Sign up to set email alerts
|

A soil sequence in the natural and reclaimed marshes of the Guadalquivir river, Seville (Spain)

Abstract: Five soil profiles from a saline zone in the province of Seville CMarismas del Guadalquivir", SW. Spain) and one from an adjacent non-saline zone, have been analyzed in order to determine their physical and chemical properties and their classification. All of these soils are recent and of fine texture. Hydraulic conductivity, except in top layers, as well as aeration porosity, is always low; non-available water holding capacity and linear extensibility, high. Differences are however found between those located… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 5 publications
0
12
0
Order By: Relevance
“…The soils were essentially classified as Aeric Endoaquepts (Soil Survey Staff, 1998). Detailed information about the area and its soils can be found elsewhere (Moreno et al., 1981; Domínguez et al., 2001). Mean temperature in the area varies from 10.0 (January) to 25.5°C (August).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The soils were essentially classified as Aeric Endoaquepts (Soil Survey Staff, 1998). Detailed information about the area and its soils can be found elsewhere (Moreno et al., 1981; Domínguez et al., 2001). Mean temperature in the area varies from 10.0 (January) to 25.5°C (August).…”
Section: Methodsmentioning
confidence: 99%
“…Crops were irrigated using sprinklers at the beginning of the cycle (two first irrigations) and by furrows during the rest of the cycle. High moisture levels in relation to the irrigation system and the low hydraulic conductivity of soils (Moreno et al., 1981; Domínguez et al., 2001) are also important factors in explaining the incidence of several diseases such as black root rot (Rothrock, 1992). Fertilizer was applied at preplant [usual rates: 52 kg N/ha, 68 kg P/ha and 43 kg K/ha, using a mixture of (NH 4 ) 2 HPO 4 , urea and KNO 3 ] and sidedress (usually 250 kg N/ha as NH 4 NO 3 ).…”
Section: Methodsmentioning
confidence: 99%
“…Moreno et al (1981) reported values of saturated hydraulic conductivity < 1 mm h -1 for the heavy clay soils of the marshes of the Guadalquivir river under rice cultivation. For the reclaimed and irrigated soils of this area Moreno et al (1995) also found values of saturated hydraulic conductivity < 1 mm h -1 at a depth below 0.5 m in the soil profile.…”
Section: Methodsmentioning
confidence: 99%
“…Due to droughts and limited water supplies in arid and semiarid regions worldwide, the reclamation of carbo‐sodic‐affected soils is important. The cultivation of naturally salt‐influenced marshland soils under Mediterranean climate conditions is of great interest because large areas are affected (Moreno et al, 1981; Sumner et al, 1998; Domínguez et al, 2001; El‐Mrabet et al, 2003). The Guadalquivir River area in southwestern Spain is a region that is dominated by clayey (illitic) Salorthidic Fluvaquents (Moreno et al, 1980; de la Rosa et al, 2009), which are characterized by high CaCO 3 contents, a high ESP of >15%, and Na adsorption ratios (SARs) of >10 mmol c L −1 .…”
mentioning
confidence: 99%